APPRECIATE THOSE ON DUTY 15 DURING HARI RAYA - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato’ Dr. Omar Osman expressed his appreciation to those who are prepared to be on duty when the Muslims are in the midst of celebrating the coming Aidil Fitri.